Relation of Liver Fibrosis Assessed by Elastography with Glycemia in Chronic Hepatitis C Patients (Medical Forum Monthly, 2020)
Objective: HCV infection is a major cause of liver fibrosis that may leads to glucose dysregulation. Elastography is a relatively new, non-invasive technique for assessment of liver stiffness. Present study aimed to find out the correlation of degree of liver stiffness with glycemia in chronic HCV patients.Study Design: Cross-Sectional StudyPlace and Duration of Study: This study was conducted at the Institute of Basic Medical Sciences of Dow University of Health Sciences, Karachi for one year.Materials and Methods: Patients were recruited by convenient sampling technique from the hepatitis clinic and medical ward of Ruth Pfau Civil Hospital, Karachi. A total of ninety participants were inducted. Among them, sixty were HCV related chronic liver disease patients (Group B) of 30-60 years of age of either gender while thirty were age and sex matched healthy control subjects (Group A). Patients not fulfilling the inclusion criteria or not willing to participate were excluded. Fasting blood glucose all participants were estimated. Based on Elastography findings HCV patients were sub-grouped into B1 (METAVIR grade FI and F2) and B2 (MATAVIR grade F3 and F4). Data entered and analyzed by SPSS version 20.0. and presented as frequency (n; %) and mean ±SD. One-way ANOVA, Post Hoc Tuckey’s test and Pearson’s correlation test were applied where appropriate. A p-value of <0.05 was considered as statistically significant.Results: Demographic and anthropometric characteristics of the study participants showed non-significant difference compared to control. Liver stiffness was found to be significant raised in advance fibrosis compared to control and early fibrosis group. Patients with advanced fibrosis had significant raised FBG compared to control (p = 0.002) and early fibrosis patients (p = 0.004). Pearson’s correlation test revealed significant moderate positive relation (r=0.393, R2=0.155) of FBG with liver fibrosis (p= 0.000).Conclusion: Liver stiffness as assessed by elastography has significant positive correlation with glycaemia in chronic HCV patients.